M10 Living with relapsing polychondritis; a patient and carer engagement exploration. (15th November 2016) - Haines, J; Hull, J; Swaison, J; Clark, T; Niven, R
Abstract : Introduction: Relapsing polychondritis (RP) is a poorly understood rare condition in which recurrent bouts of inflammation affect the cartilage of the ears, nose, larynx and tracheobronchial tree. Prospective research is extremely limited and true prevalence data unknown. There are no identified optimal diagnostic pathways and treatment is not standardised. Seeking patient experience and opinion is invaluable to support and inform clinical and research strategies. We report the first known public involvement data relating to living with RP. Method: The RP patient support group hosted a patient engagement event to provide a reciprocal education environment for healthcare professionals, sufferers and their carers. A one-hour patient and carer focus group, aiming to identify key issues relating to living with RP, was facilitated by members of the Large Airway Collapse with Symptoms (LACS) national network. The facilitators were experienced in running focus groups and had clinical awareness of RP to support discussion when needed. The semi-structured session explored: symptoms; effect on everyday life (emotional, physical, impact on others); diagnosis(time span, professionals involved, ongoing monitoring); healthcare professional support. The session concluded with a priority exercise where participants received four 'resource' coins to distribute as they wished to themed issues (as defined collectively by the group). Results: Twenty-two participated; 13 RP suffers and 9 carers. The group fully engaged and there were no conflicts, despite differing opinions. Despite some valued on-line peer support groups general consensus was provision is limited for those living with RP; the majority had never met another RP sufferer/carer until the session. Group defined themed issues for RP suffers included: lack of understanding; loss of identity; breathlessness; pain; fatigue; impact on relationships; memory impedance. Carer themed issues were similar: pain; lack of appropriate support; restrictions on planning ahead; impact on social life. The allocation of resource across the groups differed in priority (Table 1 ). Conclusion: Common issues effect both RP suffers and their carers but there are variations in the hierarchy of burden. We acknowledge this is a preliminary engagement exercise. However, the key issues identified should form the foundation for further research focus groups to guide appropriate patient-centred care for RP.